Feringhee Dharma: Augustinians, Amerindians and a Bengali deity in an early modern Iberian world. Issue 1 (2nd January 2016) - Mukharji, Projit B.
ABSTRACT: Dharma Thakur has been widely studied as a Bengali folk deity. As an exemplary 'folk' deity, scholarship on him has been resolutely focused within a discrete local space. Scholars have sought to dig deep into a local past to understand the deity and his cult. As a result, the more recent historical contexts and particularly the impact of European Christianity upon such deities have been entirely ignored. Using one of the earliest texts of the cult, viz. Rupram Chakrabarty's seventeenth-century Dharmamangal, I challenge this insular local spatiality. By first locating Rupram himself in his contemporary social and political world, I show his proximity to Portuguese settlements and Augustinian churches. I then use the material culture of foods described in the text to show Rupram's implication in an early modern Iberian world. In the last two sections, I delve into narrative episodes of the text that reveal complex theological dialogues not only with Portuguese Catholicism, but also indirectly with distant Amerindian shamans. In conclusion, I argue that we need to trace the horizontal connections of folk religion in the early modern world, rather than persisting in the quest for a deep past.